Determination of viscohyperelastic properties of tubule epithelial cells by an approach combined with AFM nanoindentation and finite element analysis. (February 2020) - Wang, Lei; Tian, Liguo; Wang, Ying; Zhang, Wenxiao; Wang, Zuobin; Liu, Xianping
Abstract: Tubule epithelial cell is a complex element that not only exhibits elasticity behaviour, but also presents nonlinear and time-dependent behaviour during any stage of its life cycle. Responses of tubule epithelial cells to physical stimuli are influenced by their mechanical properties. However, accurately constitution of their mechanical properties is still a challenge and the characterisation mechanism is far from sophisticated. In addition, the particular mechanism that determines the mechanical response is still unclear. In order to overcome this limit, an approach combined with AFM nanoindentation experiment and computation modelling by a viscohyperelastic model is developed to describe the complex behaviour in the current study. Viscohyperelastic parameters of tubule epithelial cells treated and untreated with drug Cytochalasin D are obtained by the optimization algorithm applied in this approach. The comparison between treated and untreated results indicate that larger amount of relaxation was observed due to the disruption of cytoskeleton when using drug Cytochalasin D. Our results demonstrate the feasibility of this approach to monitor the variation of these viscohyperelastic parameters, which can be used as an effective index for renal disease diagnosed and drug evaluation.